2021
DOI: 10.1108/jhr-09-2020-0395
|View full text |Cite
|
Sign up to set email alerts
|

Healthy aging in India: evidence from a panel study

Abstract: PurposeRecent public health policy emphasizes the achievement of healthy aging as average life expectancy increases worldwide. Evidence for healthy aging from low- and middle-income countries (LMIC) is limited. The purpose of this paper is to assess the prospects of healthy aging and its associated factors in the Indian context.Design/methodology/approachThe study was based on a national-level panel survey, the Indian Human Development Survey (IHDS) conducted in 2004-05 and 2011-12. The analytical sample consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…showed that persons aged 60-79 had almost 8 the hazard of developing multimorbidity in comparison with those aged 18-39. Similar results were also reported by others (Chau et al, 2021;Fabbri et al, 2015b;Irshad and Dash, 2022;Li et al, 2021;Moin et al, 2021;Mounce et al, 2018;Ryan et al, 2018;Schäfer et al, 2019;Seo, 2019;Vall Castelló and Tubianosa, 2020). Lu et al (Lu et al, 2021).…”
Section: Synthesis Of the Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…showed that persons aged 60-79 had almost 8 the hazard of developing multimorbidity in comparison with those aged 18-39. Similar results were also reported by others (Chau et al, 2021;Fabbri et al, 2015b;Irshad and Dash, 2022;Li et al, 2021;Moin et al, 2021;Mounce et al, 2018;Ryan et al, 2018;Schäfer et al, 2019;Seo, 2019;Vall Castelló and Tubianosa, 2020). Lu et al (Lu et al, 2021).…”
Section: Synthesis Of the Resultssupporting
confidence: 90%
“…Female sex was found to be associated with an increased risk of developing multimorbidity in 4 studies (Bisquera et al, 2022;Hussin et al, 2019;Moin et al, 2021;Quinones et al, 2016), whereas others (Schäfer et al, 2019;Vall Castelló and Tubianosa, 2020) found female sex was protective. No association between sex and multimorbidity was found by other authors (Chau et al, 2021;Irshad and Dash, 2022;Melis et al, 2014;Mounce et al, 2018;Poole and Steptoe, 2018;van den Akker et al, 2000).…”
Section: Comorbid Cvd and Diabetesmentioning
confidence: 62%
See 3 more Smart Citations